Clinical outcomes associated with guideline-discordant management of asymptomatic bacteriuria and urinary tract infection in hospitalized patients with neurogenic bladder - Margaret A. Fitzpatrick; Marissa Wirth; Jimmy Nguyen; Katie J. Suda; Frances M. Weaver; Stephen Burns; Eileen Collins; Nasia Safdar; Ursula Patel; Charlesnika T. Evans (Cambridge University Press, 2022)
Abstract Objective: To compare clinical outcomes associated with appropriate and inappropriate management of asymptomatic bacteriuria (ASB) and urinary tract infection (UTI) among inpatients with neurogenic bladder (NB). Design: Multicenter, retrospective cohort. Setting: The study was conducted across 4 Veterans' Affairs hospitals. Participants: The study included veterans with NB due to spinal cord injury or disorder (SCI/D), multiple sclerosis (MS), or Parkinson's disease (PD) hospitalized between January 1, 2017, and December 31, 2018, with diagnosis of ASB or UTI. Interventions: In a medical record review, we classified ASB and UTI diagnoses and treatments as appropriate or inappropriate based on national guidelines. Main outcome measures: Frequencies of Clostridioides difficile infection, acute kidney injury, 90-day hospital readmission, postculture length-of-stay (LOS), and multidrug-resistant organisms in subsequent urine cultures were compared between those who received appropriate and inappropriate management. Results: We included 170 encounters with ASB (30%) or UTI (70%) diagnoses occurring for 166 patients. Overall, 86.1% patients were male, 47.6% had SCI/D and 77.6% used bladder catheters. All ASB encounters had appropriate diagnoses, and 96.1% had appropriate treatment. In contrast, 37 UTI encounters (31.1%) had inappropriate diagnoses and 61 (51.3%) had inappropriate treatment, including 30 encounters with true ASB. Among patients with SCI/D or MS, appropriate ASB or UTI diagnosis was associated with a longer postculture LOS (median, 14 vs 7.5 days; P = .02). We did not detect any significant associations between appropriate versus inappropriate diagnosis and treatment and other outcomes. Conclusions: Almost one-third of UTI diagnoses and half of treatments in hospitalized patients with NB are inappropriate. Opportunities exist to improve ASB and UTI management in patients with NB to minimize inappropriate antibiotic use.